Traduction et diversité culturelle - Jolicoeur, Louis (Romanica Silesiana)
Louis Jolicoeur makes reflections on the publishers politics within the scope of translation in the epoque of globalism and cultural domination of the United States of America, leading to the cultural crypto-colonisation which he names after M. Cronin a clonisation. Keywords : literary translation; globalization; clonisation; editing policy <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />